International Study and Attachment. - Offerdahl, Emily (My University, 2009)
Is students' participation in study abroad programs associated with their emotional attachment to important others? We hypothesize that students who are securely attached, compared to those who are not, will be more interested in or have more experience participating in study abroad programs. To test our hypothesis, undergraduate students completed on-line questionnaires that measure interest in and experience studying abroad and attachment status.
Color poster describing research conducted by Emily Offerdahl, advised by Catya von Karolyi.
Keywords: Attachment behavior; Foreign study--Psychological aspects; Posters